Sistem Informasi Karyawan Berbasis Web pada PT. Yamani Lautan Berkah Jambi - Pradipta , Rahman; Effiyaldi, Effiyaldi (LPPM Universitas Dinamika Bangsa, 2023)
Yamani Lautan Berkah Jambi is one of the private companies engaged in ship agency services by serving inter-island sea freight services (domestic), export and import. There is no good HRM/Staff and is considered very less than optimal where the process is still manual and the number of employees available. As for the obstacles that are often faced in the HRM/Staff process ranging from the process of hiring new employees, employee data updates, leave application processes, warning letters, duty letters, and the creation of employee pay slips that are still done manually with recording / creation using agenda books and Ms. Word / Ms. Excel that causes these files often damaged and lost so that it takes a long time when needed. The purpose of this research is to analyze and design Web-Based Employee Information Systems at PT. Yamani Lautan Berkah Jambi for the problems that are being faced. Data collection is done by interview method to the director and HRD section. In addition, system modeling methods using UML (Unified Modelling Language) include: usecase diagrams, activity diagrams, and class diagrams and Balsamiq Mockups to design user interfaces. The output of this research is in the form of a Design or Prototype of a Web-Based Employee Information System at PT. Yamani Lautan Berkah Jambi